PENGARUH IMPLEMENTASI GREEN ACCOUNTING DAN CORPORATE SOCIAL RESPONSIBILITY DISCLOSURE TERHADAP PROFITABILITAS: (THE EFFECT OF GREEN ACCOUNTING AND CORPOATE SOCIAL RESPONSIBILITY DISCLOSURE IMPLEMENTATION ON THE PROFITABILITY) - Salsabila, Neva; Romadhon, Fitri; Fitri, Alfiana (e-Journal Ekonomi Bisnis dan Akuntansi, 2026)
This research was motivated by stakeholders' doubts in assessing the company's seriousness in contributing to the environment and unclear allocation of funds for environmental activities. This research aims to determine the effect of implementing green accounting and CSR disclosure on profitability in food and beverage companies listed on the Indonesia Stock Exchange from 2020 to 2022. The sample in this study used a purposive sampling technique to obtain a sample of 24 food and beverage companies. The data analysis technique in this research is multiple linear analysis using SPSS 25. The results of this research are that there is no influence between green accounting and profitability with a significant value of 0.062 which is greater than 0.05, while for the CSR disclosure variable there is an influence on profitability with a value significant 0.041 which is smaller than 0.05.